STUDI TERHADAP TINDAK PIDANA KEHUTANAN DALAM PENEBANGAN HUTAN DILUAR RENCANA KERJA TAHUNAN PADA PEMILIK IZIN USAHA PEMANFAATAN HASIL HUTAN KAYU - Alasman Mpesau (Audito Comparative Law Journal (ACLJ), 2021)
The problems in this study is deforestation outside the Annual Work Plan (RKT) on Timber Product Utilization Business License owner (IUPHHK) as acts against forestry administration law based on article 74 Government Role Number 6 of 2007. However, if it is viewed from its effect on the destruction of forest which is done without planning, logging area map, work target in Annual Work Plan (RKT) can destruct the forest.  This research is a descriptive analysis which describe the problems in this research, then the analysis is carried out based on the principles of criminal law and forestry legislation.  Deforestation acts outside the Annual Work Plan (RKT) on Timber Product Utilization Business License owner (IUPHHK) is forestry criminal law based on Article 50 Chapter (2) of Law Number 41 of 1999 of forestry. It becaused permission of the forest cultivation is in only refers to certain area. Therefore, if it is done outside the mentioned area, it is categorized as illegal logging and it can destruct the forest.